2015
DOI: 10.1017/s0950268815002162
|View full text |Cite
|
Sign up to set email alerts
|

Assessing risk factors of sporadicCampylobacterinfection: a case-control study in Arizona

Abstract: Case-control studies of sporadic Campylobacter infections have predominately been conducted in non-Hispanic populations. In Arizona, rates of campylobacteriosis have been historically higher than the national average, with particularly high rates in Hispanics. In 2010, health departments and a state university collaborated to conduct a statewide case-control study to determine whether risk factors differ in an ethnically diverse region of the United States. Statistically significant risk factors in the final m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
(42 reference statements)
1
6
0
Order By: Relevance
“…We also confirm Friedman et al's, 2004 finding that whole cuts of meat (other than poultry) purchased for home use are not significant drivers of campylobacteriosis risk. As in prior case-control studies, we find that fruits, other than berries, are associated with lower risk (Baker et al, 2006;Friedman et al, 2004;Progreba-Brown et al, 2016). In contrast to prior US studies, but consistent with prior European studies, we find that fresh berries purchased for use at home did increase campylobacteriosis risk (Kuhn et al, 2018;Wingstrand et al, 2006).…”
Section: Lessons Learnedsupporting
confidence: 88%
“…We also confirm Friedman et al's, 2004 finding that whole cuts of meat (other than poultry) purchased for home use are not significant drivers of campylobacteriosis risk. As in prior case-control studies, we find that fruits, other than berries, are associated with lower risk (Baker et al, 2006;Friedman et al, 2004;Progreba-Brown et al, 2016). In contrast to prior US studies, but consistent with prior European studies, we find that fresh berries purchased for use at home did increase campylobacteriosis risk (Kuhn et al, 2018;Wingstrand et al, 2006).…”
Section: Lessons Learnedsupporting
confidence: 88%
“…Among the several species known to potentially cause pathogenesis in humans, C. jejuni and C. coli were implicated in over 90% of reported human campylobacteriosis worldwide ( Sheppard et al, 2009 ). The majority of cases with infection displayed watery or bloody diarrhea and abdominal cramps that could be accompanied by other symptoms including fever, vomiting and headaches ( Pogreba-Brown et al, 2016 ). In addition, Campylobacter related infections may also result in extraintestinal manifestations such as bacteremia, meningitis, abortion and mycotic aneurysms and long-term complications like the Guillain-Barré syndrome and reactive arthritis ( O’Brien, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, contaminated foodstuffs of poultry play the most significant role in the transmission of Campylobacter spp. to humans, although contaminated water and other foodstuff including milk, dairy products and red meats have been also recognized as potential source ( Sheppard et al, 2009 ; Pogreba-Brown et al, 2016 ; Thépault et al, 2018 ). In addition, the presence of Campylobacter spp.…”
Section: Introductionmentioning
confidence: 99%
“…This may indicate that in Arizona, exposure to Campylobacter is more wide-spread across a variety of food exposures, again, making these cases a good choice as ‘controls’ compared with a variety of enteric pathogens. Foods such as poultry and queso fresco, which previous studies in the state have shown to be associated with Campylobacter [16], are also more likely to be reported as such here. Eggs, often associated with Salmonella , were not associated in this dataset, even when examined by serotype.…”
Section: Discussionmentioning
confidence: 81%